1993
DOI: 10.1016/0304-3940(93)90878-o
|View full text |Cite
|
Sign up to set email alerts
|

Basal extracellular dopamine in the nucleus accumbens during amphetamine withdrawal: a ‘no net flux’ microdialysis study

Abstract: The basal extracellular concentration of dopamine in the nucleus accumbens was quantified using the 'no net flux' microdialysis method, in rats undergoing withdrawal from D-amphetamine. Rats were initially pretreated with saline, or an escalating dose amphetamine regimen known to produce a robust withdrawal syndrome, and extracellular dopamine was quantified 3 or 28 days after the last pretreatment injection. There was no effect of amphetamine pretreatment on the basal extracellular concentration of dopamine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
27
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 14 publications
6
27
1
Order By: Relevance
“…There is evidence that the effects of antipsychotic drugs on LI are mediated in the nucleus accumbens (Gray et al 1997); furthermore, reports of reduced DA function in the nucleus accumbens during COC and AMPH withdrawal (Parsons et al 1991;Rossetti et al 1992;Weiss et al 1992Weiss et al , 1997Kuhar and Pilotte 1996) are consistent with the idea that enhanced LI reflects DA antagonism in mesolimbic targets during pre-exposure and/or avoidance testing. Nevertheless, reductions in nucleus accumbens DA during psychostimulant withdrawal are not reported by all laboratories and may be dependent on schedules of drug administration or procedural details (Crippens et al 1993;Crippens and Robinson 1994); in particular, it is very possible that the schedule of low-dose AMPH employed in this study would not have been sufficient to reduce accumbens DA during withdrawal. Finally, in an earlier study in which COC was administered subsequent to CS pre-exposure and CS-UCS conditioning, we also observed enhanced LI of conditioned freezing behavior during COC withdrawal (Murphy et al 2001).…”
Section: Discussionmentioning
confidence: 87%
“…There is evidence that the effects of antipsychotic drugs on LI are mediated in the nucleus accumbens (Gray et al 1997); furthermore, reports of reduced DA function in the nucleus accumbens during COC and AMPH withdrawal (Parsons et al 1991;Rossetti et al 1992;Weiss et al 1992Weiss et al , 1997Kuhar and Pilotte 1996) are consistent with the idea that enhanced LI reflects DA antagonism in mesolimbic targets during pre-exposure and/or avoidance testing. Nevertheless, reductions in nucleus accumbens DA during psychostimulant withdrawal are not reported by all laboratories and may be dependent on schedules of drug administration or procedural details (Crippens et al 1993;Crippens and Robinson 1994); in particular, it is very possible that the schedule of low-dose AMPH employed in this study would not have been sufficient to reduce accumbens DA during withdrawal. Finally, in an earlier study in which COC was administered subsequent to CS pre-exposure and CS-UCS conditioning, we also observed enhanced LI of conditioned freezing behavior during COC withdrawal (Murphy et al 2001).…”
Section: Discussionmentioning
confidence: 87%
“…Specifically, an attenuation of LI has been linked to increased DA activity in the nucleus accumbens (Solomon and Staton 1982;Gray et al 1997). In contrast, previous reports have indicated that AMPH withdrawal is associated with either a reduction or no change in basal DA levels (Rossetti et al 1992;Segal and Kuczenski 1992;Crippens et al 1993;Paulson and Robinson 1995;Weiss et al 1997). Similarly, studies from our lab using in vivo microdialysis have indicated unchanged basal levels of DA in both the core and shell subregions of the nucleus accumbens on day 4 of withdrawal from the escalating dose schedule of AMPH used in this study (Pezze et al In press).…”
Section: Discussionmentioning
confidence: 90%
“…Increased DA release in the nucleus accumbens after an AMPH challenge has been repeatedly found in sensitized rats (Robinson and Becker 1986; but see Segal and Kuczenski 1992) and numerous studies have shown that both LI and PPI are disrupted by DA agonists (Swerdlow et al 1992;Weiner and Feldon 1997;Geyer et al 2001). However, basal levels of nucleus accumbens DA are reportedly reduced or unchanged during AMPH withdrawal (Rossetti et al 1992;Segal and Kuczenski 1992;Crippens et al 1993). Our laboratory has in fact shown that rats withdrawn from the AMPH schedule used in the present study showed no differences in basal DA levels, but decreased DA efflux in the shell, and increased DA efflux in the core of the nucleus accumbens during the expression of a conditioned fear response (Pezze et al 2002).…”
Section: Discussionmentioning
confidence: 99%